To burn-out or not to burn-out: a cross-sectional study in healthcare professionals in Spain during COVID-19 pandemic - Mariano Provencio; Maria Torrente; Pedro AC Sousa; Ana Sánchez-Ramos; Joao Pimentao; Ana Royuela; Fabio Franco; Ana Collazo-Lorduy; Ernestina Menasalvas (BMJ Open)
Objective To assess the prevalence of burn-out syndrome in healthcare workers working on the front line (FL) in Spain during COVID-19.Design Cross-sectional, online survey-based study.Settings Sampling was performed between 21st April and 3rd May 2020. The survey collected demographic data and questions regarding participants’ working position since pandemic outbreak.Participants Spanish healthcare workers working on the FL or usual ward were eligible. A total of 674 healthcare professionals answered the survey.Main outcomes and measures Burn-out syndrome was assessed by the Maslach Burnout Inventory-Medical Personnel.Results Of the 643 eligible responding participants, 408 (63.5%) were physicians, 172 (26.8%) were nurses and 63 (9.8%) other technical occupations. 377 (58.6%) worked on the FL. Most participants were women (472 (73.4%)), aged 31–40 years (163 (25.3%)) and worked in tertiary hospitals (>600 beds) (260 (40.4%)). Prevalence of burn-out syndrome was 43.4% (95% CI 39.5% to 47.2%), higher in COVID-19 FL workers (49.6%, p<0.001) than in non- COVID-19 FL workers (34.6%, p<0.001). Women felt more burn-out (60.8%, p=0.016), were more afraid of self-infection (61.9%, p=0.021) and of their performance and quality of care provided to the patients (75.8%, p=0.015) than men. More burn-out were those between 20 and 30 years old (65.2%, p=0.026) and those with more than 15 years of experience (53.7%, p=0.035).Multivariable logistic regression analysis revealed that, working on COVID-19 FL (OR 1.93; 95% CI 1.37 to 2.71, p<0.001), being a woman (OR 1.56; 95% CI 1.06 to 2.29, p=0.022), being under 30 years old (OR 1.75; 95% CI 1.06 to 2.89, p=0.028) and being a physician (OR 1.64; 95% CI 1.11 to 2.41, p=0.011) were associated with high risk of burn-out syndrome.Conclusions This survey study of healthcare professionals reported high rates of burn-out syndrome. Interventions to promote mental well-being in healthcare workers exposed to COVID-19 need to be immediately implemented.